2013
DOI: 10.1038/npp.2013.189
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Reward-Based Spatial Learning in Persons with Cocaine Dependence

Abstract: Dysfunctional learning systems are thought to be central to the pathogenesis of and impair recovery from addictions. The functioning of the brain circuits for episodic memory or learning that support goal-directed behavior has not been studied previously in persons with cocaine dependence (CD). Thirteen abstinent CD and 13 healthy participants underwent MRI scanning while performing a task that requires the use of spatial cues to navigate a virtual-reality environment and find monetary rewards, allowing the fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 55 publications
3
27
0
Order By: Relevance
“…42 Dopaminergic dysfunction in reward circuits is documented in adults with both SUDs 24 and BN. 43 Cocaine-dependent men also show altered functioning of reward circuitry on our spatial task, 25 further pointing to dopaminergic, reward-circuit dysfunction in both disorders. Such functional abnormalities may influence the initial learning of binge-purge behaviors, consistent with the role of VS in the early stages of reinforcement-based learning 8 (in drug addiction 7 ).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…42 Dopaminergic dysfunction in reward circuits is documented in adults with both SUDs 24 and BN. 43 Cocaine-dependent men also show altered functioning of reward circuitry on our spatial task, 25 further pointing to dopaminergic, reward-circuit dysfunction in both disorders. Such functional abnormalities may influence the initial learning of binge-purge behaviors, consistent with the role of VS in the early stages of reinforcement-based learning 8 (in drug addiction 7 ).…”
Section: Discussionmentioning
confidence: 78%
“…25 These findings from adolescents with BN point to functional abnormalities within anterior hippocampus and fronto-striatal regions associated with reward-based learning and suggest that an increased sensitivity to positive PEs, together with deficient engagement of inferior frontal cortices, may contribute to the purported imbalance between top-down control and more bottom-up reward circuits that characterizes eating disorders. 44 Indeed, abnormal activation of anterior hippocampus and VS during the receipt of unexpected rewards (and increased sensitivity to positive PEs) in adolescents with BN suggests altered bottom-up representations of action–outcome associations that may contribute to the learned associations between food cues and maladaptive binge-eating behaviors.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The third goal of the current study was to test whether ACD prefrontal impairment was related to an altered frontostriatal connectivity pattern, as previous studies have suggested [32,33]. We computed a psychophysiological analysis using the left DLPFC as a seed region because it was the only area that showed between-group differences in sensitivity to reward gradients in the PFC.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study also discovered that in students who were referred to a college alcohol and drug assistance program, polydrug (containing club drugs such as methamphetamine, LSD and ketamine) cues produced significantly greater left inferior temporal gyrus activity compared with neutral cues [94]. Cocaine-dependent participants had increased neural functioning of the left inferior Disrupted Resting-State Brain Functional Architecture in Amphetamine-Type Stimulant Abusers temporal gyrus in the "reward" compared to the "no-reward" condition during reward-based spatial learning (a form of episodic memory) [95]. In comparison to a placebo, the left inferior temporal gyrus of those who used designer drugs containing benzylpiperazine (a worldwide safe and legal alternative to illicit recreational drugs, such as MDMA and methamphetamine) showed decreased activation in a Stroop task, especially during the incongruent condition [96].…”
Section: Research Qun Chenmentioning
confidence: 99%